Rancang Bangun Sistem Informasi Jurnal Perkuliahan Berbasis Web Guna Meningkatkan Efektivitas Pembelajaran - Erika Ocha Widya Susanti; Izzatul Ummami; Winarti Winarti (Prodi Sistem Informasi Universitas Dharma Andalas, 2022)
The lecture journal is a document that contains a description of the lecture material in each lesson. Lecture journals are used to monitor and review the learning process, especially in the Informatics Engineering study program. It is hoped that the existence of this lecture journal is able to increase the effectiveness of learning. In addition, it can lighten the burden for those who recapitulate student activities. Because the researcher wants to design a lecture journal in the form of a website so that it can be opened by all elements, both students, lecturers, deans, heads of departments, and admins. This research is motivated because the lecture journals at Darul Ulum University, especially in the Informatics Engineering study program, are still offline, which are still in the form of paper. With the problems that occur, researchers will design a website that can be used for the development of lecture journals. The website that will be used is designed using the waterfall method and uses a UML design model in the form of use case diagrams and activity diagrams. Using the PHP programming language and MySQL database in the form of a lecture journal that can be filled out online during lectures.